KESADARAN ORANGTUA NELAYAN TERHADAP PENDIDIKAN AGAMA ANAK: STUDI KASUS DI MASYARAKAT TAMBAK LOROK SEMARANG - Anas; Ikhrom; Agus Sutiyono (GoAcademica Research dan Publishing, 2023)
Discussions on the low level of the economy of fishing communities are often associated with low education, social care and backwardness of the community, not many of which relate it to awareness in educating children's religion. For this reason, this article aims to reveal the awareness of parents in introducing, facilitating and financing their children's religious education. This qualitative research uses a phenomenological approach that relies on observation, interviews and documentation. The results of the study showed (a) the awareness of parents (husbands) in educating children at home was hindered by their busy lives as fishermen, generally mothers who educate children, (b) the role of religious leaders in educating children has an important role in the social community, (c) the form the religious behavior of fishermen's children was born because of the habits that exist in the fishing community.